Model Ontologi Representasi Pengetahuan untuk Pengorganisasian Sumber Daya Pengetahuan - I, Istiadi; Nugroho, Lukito Edi; Adji, Teguh Bharata (2012)
The growing availability of knowledge materials requires organizing to support improvement of a personal knowledge. These organizer need the representation of knowledge as base of processing. This paper aims to show modeling of knowledge representation to support organizer use ontology approach. The concept of model is viewed as the set of object in the hierarchy of Knowledge Domain Class, Knowledge Section Class and up to Knowledge Object Class level. Relations between concepts are designed to be paired with its inverse that allows data tracking on forward and backward directions. Standard Web Ontology Language (OWL) that compatible to be accessed by the computer processing is used as a medium implementation its representation. Furthermore the model was tested with a query mechanism for obtaining the data or information related to the expected objects.